Pengaruh Good Corporate Governance Terhadap Corporate Social Responsibility pada Perusahaan Sub Sektor Transportasi - Noriko Thasya; Lisah Lisah; Angeline Angeline; Natasyah Gozal; Veronica Veronica; Namira Ufrida Rahmi (Jurnal Samudra Ekonomi dan Bisnis, 2020)
This study aims to examine the effect of Good Corporate Governance on Corporate Social Responsibility (CSR). The population used is the transportation sub-sector companies listed on the Indonesia Stock Exchange period 2014 - 2018, amounting to 37 companies. Purposive sampling was used to obtain 8 companies as research samples. Data used in the form of annual reports published by the companies, and analyzed using multiple linear regression. The results indicate that simultaneously, Audit Committee, the Board of Commissioners, Institutional Ownership and Independent Commissioners prove to have a significant effect on CSR. However, the results of statistical tests prove that partially, the Audit Committee and Institutional Ownership have a significant negative effect on CSR; The Board of Commissioners has positive and significant influence on CSR; and Independent Commissioners have a negative but not significant effect on CSR.